Peanut Growth and Gynophore Formation on Boron and Phosphor Applications - Novita Rahman; Suntoro Suntoro; Amalia Tetrani Sakya (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2019)
Soil is an important factor in peanut cultivation as a nutrient provider. In recent years, peanut production has dwindled due to the decrease in soil fertility. Boron as a micronutrient can maximize peanut production through optimum viability of flowers and phosphor as essential nutrients for peanut to improve its pod filling. This study aims to examine the application of boron and phosphor growth and formation of peanut gynophore. The research was conducted from September 2017 to January 2018 in Sambirembe village, Magetan. The experiment uses randomized complete block design (RCBD) with the first factor applied on the dose of boron fertilizer (0, 1, 2 3 kg ha-1) and the second was on the dose of phosphor fertilizer (0, 75, 100, 150 kg ha-1), repeated 3 times. Boron application resulted in the highest plant height at the fourth week by 10.45%. The application of 1 kg ha-1 boron without phosphorus (0 kg ha-1) yielded the highest gynophore formation, i.e. 42 gynophore formation.